PELATIHAN PEMBUATAN CASH REGISTER BAGI PELAKU USAHA UMKM DI WILAYAH WISATA KEK MANDALIKA - Pahmi, Saepul; Fitri, Syarifah Massuki; Pratiwi, Widya; Aini, Baiq Quratul; Yuspiadi, Yuspiadi (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
The existence of MSMEs in Indonesia has been able to become an important pillar of the national economy for many years by absorbing labor, providing goods needed by the community, and contributing to the country through taxes. However, this does not mean that MSMEs are without obstacles and problems. One of the problems that MSMEs often face is the ability to prepare adequate financial reporting for themselves. The majority of MSMEs still have very little knowledge about bookkeeping, which is very important for the progress and development of MSMEs in the future. For this reason, the training activity on making cash registers for MSME business actors in the Mandalika SEZ area was held with the aim of helping to provide useful knowledge and knowledge for MSME business actors. The direct impact of this cash register training is that MSME business actors can understand how to compile a daily cash book which they need as important information so that they can continue to monitor and control the receipts and expenses of their business.